Odpowiedzi

2009-12-09T15:32:40+01:00
A)= (8(skrocic na 1)/7*7/8(skrocic na 1)-3/2)*4/9=(7/3-3/2)*4/9= (9/6-6/6)84/9=3(skacamy na 1)/6(skracamy na 3)*4(skracamy na 2)/9(skracamy na 3)= 2/9
b) 31/6: [12/1 *(31/6+3/4)]= 31/6: [12/1: ( 35/24+9/24)]= 31/6:[12/1*44/24]=31/6:(12/1*24/44)=31/6(skrocic na 1):288(skrocic na 48)/44= 1364/48=28 41/48.
2009-12-09T15:38:41+01:00
A) (8/3×7/8 - 3/2) ×4/9=(7/3 - 3/2) ×4/9=(14/6 -9/6)× 4/9=5/6×4/9=20/54=10/27
b) 31/6÷[12×(11/6+3/4)]=31/6÷[12×(22/12+9/12)]=31/6÷[12×31/12]=31/6÷31=31/6×1/31=1/6